MEASUREMENT OF SERVICE QUALITY PERCEPTION, CUSTOMER SATISFACTION, AND CUSTOMER LOYALTY IN PT MEDIKA ANTAPANI - Annisaa Thaharoh, Yustia
In 2020, there were 11,347 clinics in Indonesia, consisting of 10,238 Pratama Clinic and 1,109 Utama Clinic. In 2021, there were 6,572 Pratama clinics and 1,042 Utama clinics, with West Java Province having the most number of clinics. PT. Medika Antapani is a private company that provides public health services in Bandung, Jawa Barat, including essential general services, specialists, home care services, drug rehabilitation, pharmacy, Imunicare, and independent midwife practice. The number of customer visits has decreased in 2020 and 2021 and exacerbated in 2022 due to the transfer of general practitioner services to KPMA in 2022. As a result, the decrease in cash customer visits affected the decrease in profit income. Additionally, the number of Pratama clinics in the Kiaracondong area has almost doubled to 15 clinics, making cash clients many choices for Pratama clinics. Health services are required to always improve the quality of service to provide satisfaction which will affect customer loyalty in order to compete with its competitors. This research aims to help PT. Medika Antapani meets what customer needs and want in service to increase satisfaction and increase customer loyalty. The author adopts a conclusive research design to address the research questions in this study. Conclusive research design is a study design that focuses on measuring clearly defined marketing phenomena. The author collects primary data by distributing research questionnaires using a Likert scale to 200 respondents who must satisfy the following requirements: 1. Having obtained services from the company, 2. Paying from their own pocket. This study employs a descriptive and causal research technique to examine variables and provide a systematic, factual explanation of the facts and relationship between them. The results of descriptive analysis obtained from 200 respondents, that most respondents are male, with an age category of 60-74, live in Cisaranten Endah, have an employee profession, and use general practitioner services at PT Medika Antapani. For causal analysis, the following results were obtained the total average: the service quality variable is 3.088, the satisfaction variable is 3.127, and the loyalty variable is 2.93. This loyalty variable is greatly influenced simultaneously by the satisfaction and service quality variables which reach 84.1%. These findings support the business issues that exist in PT. Medika Antapani has experienced a decrease in visits since 2018 which is marked by a lack of loyalty. So to increase the value of loyalty, it must be started with improvements in service quality variables. The implementation plan for PT. Medika Antapani outlines six elements and improvements that can be made immediately such as low scores regarding the latest equipment, recruiting Ob-Gyn doctors, and providing reminder message service. The difficult improvement is to improve the dimensions of Pratama Clinic which has a large number of competitors, and moreover, there has just been a unification of all clients to Pratama Clinic which makes clients complain about queuing. Besides that, this improvement requires a lot of time and money, and many departments are involved. For future recommendations, it is expected to PT Medika Antapani also has to evaluate its services every year or twice a year regarding client satisfaction. This evaluation is used to always maintain the quality of the services provided and can make developments in the right fields needed by service users.